Groundwater quality assessment around Lake Mkpitime, Nigeria, using integrated geophysical and hydrochemical approaches (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Groundwater quality assessment around Lake Mkpitme has not received any investigations. The goal of this study was to apply integrated geophysical and hydrochemical approaches to investigate the suitability of the groundwater around the lake for domestic, agricultural and industrial sustainable use. Ten vertical electrical soundings (VES) were conducted within the lake vicinity, while four groundwater samples and seven lake samples were collected for water quality assessment. The VES result revealed an aquifer depth range of 14.8 – 108 m, located within the fourth layer, while the aquifer resistivity ranged from 645 – 5287 ?m. Dar-Zarrouk parameters evaluation revealed values of longitudinal conductance (0.03-0.213 ?-1), transmissivity (1.94-98.62 m2/day), transverse resistance (47247-313525 ?m2), indicating an aquifer with poor to intermediate protective capacity and low to intermediate potential. The hydrochemical analysis of groundwater samples revealed dominant Ca2+ - Na+ - HCO3- - Cl- - SO42- water facies, while the lake samples revealed Ca2+ - Na+ - HCO3- Cl- - SO42- water facies, indicating water mixing and suggestive of lake and groundwater interaction, as groundwater close to the lake has higher concentrations and possible stratification of water chemistry with depth. The fresh water nature of groundwater was revealed by the maximum TDS range of 10.8-19.3 mg/l, while that of the lake ranged from 10.8-31.3 mg/l, implying fresh-moderate subsurface mineralization, with groundwater that is within the permissible limit of the World Health Organization. The results showed that the groundwater quality around the lake is suitable and sustainable for both domestic, agricultural and industrial needs.
Keywords: coastal aquifer; groundwater; integrated assessment; Lake Mkpitime; Niger Delta; sustainable water supply